2003
DOI: 10.1103/physrevc.67.052202
|View full text |Cite
|
Sign up to set email alerts
|

Theppppπ+πrea

Abstract: Exclusive measurements of the pp → ppπ + π − reaction have been carried out at Tp = 775 MeV at CELSIUS using the PROMICE/WASA setup. Together with data obtained at lower energy they point to a dominance of the Roper excitation in this process. From the observed interference of its decay routes N * → N σ and N * → ∆π → N σ their energy-dependent relative branching ratio is determined.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Starting first with the WASA/PROMICE detector setup, followed by the completed WASA detector at CELSIUS and finally at COSY all ppinduced, i.e. isovector two-pion production channels from threshold up to √ s = 2.5 GeV have been studied [323,324,325,326,327,328,329,330,331] complemented by a corresponding program with polarized beam at COSY-TOF [314,332]. The results for the total cross sections are shown in Fig.…”
Section: No Dibaryon Signal In Pp-induced Two-pion Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Starting first with the WASA/PROMICE detector setup, followed by the completed WASA detector at CELSIUS and finally at COSY all ppinduced, i.e. isovector two-pion production channels from threshold up to √ s = 2.5 GeV have been studied [323,324,325,326,327,328,329,330,331] complemented by a corresponding program with polarized beam at COSY-TOF [314,332]. The results for the total cross sections are shown in Fig.…”
Section: No Dibaryon Signal In Pp-induced Two-pion Productionmentioning
confidence: 99%
“…By fine adjustments of the resonance parameters in the Valencia model calculations all differential distributions could be quantitatively described by the conventional process of t-channel meson exchange leading to the excitation of the Roper resonance close to threshold followed at higher energies by the excitation of the ∆∆ system. It has been demonstrated that the Roper excitation and its decay via the interfering routes N * → N σ → N ππ and N * → ∆π → N ππ lead to very characteristic patterns in the differential distributions, especially in the ππ invariant-mass distribution [314,323,325,326]. In the ∆∆ region it is in addition the pπ invariant mass distributions, which exhibit a characteristic pattern [329].…”
Section: No Dibaryon Signal In Pp-induced Two-pion Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shown in Fig. 54 are the points obtained by the COSY-TOF collaboration [179] and values from an early version of WASA at CELSIUS [180]. These data seem to behave more or less like phase space, whose dependence is shown by the shaded area.…”
Section: 1 Two-pion Production In Proton-proton Collisionsmentioning
confidence: 98%
“…Total cross section for the pp → ppπ + π − reaction as a function of the proton beam energy. Closed (red) circles are WASA data taken at CELSIUS [180] whereas the (blue) squares were obtained by the collaboration at COSY. A collection of older data is also shown [181].…”
Section: 1 Two-pion Production In Proton-proton Collisionsmentioning
confidence: 99%